A novel approach for adsorption of organic dyes from aqueous solutions using a sodium alginate/titanium dioxide nanowire doped with zirconium cryogel beads - Azeroual, Sana; Khatib, Khalid; Belfkira, Ahmed; Ablouh, El-Houssaine; Hanani, Zouhair; Taourirte, Moha; Jalal, Rachid (Frontiers in Chemistry, 2024)
The presence of organic dyes in wastewater raises significant environmental and human health concerns, owing to their high toxicity. In light of this, a novel adsorbent material with porous cryogel architecture was developed and employed for the effective removal of organic dyes from an aqueous solution. Initially, a titanium dioxide nanowire doped with zirconium HZTO was synthesized by the hydrothermal process. Subsequently, the beads (SA/HZTO) of sodium alginate and HZTO were successfully prepared through a cross-linking process, employing Ca2+ ions as the crosslinking agent. Structural analysis of SA/HZTO beads was performed using FTIR, SEM, and EDX techniques. We systematically examined the impact of different conditions, including the initial dye concentration, pH, contact time, and adsorbent dosage, on the adsorption process. Batch experiments, both in signal and binary systems, were conducted to rigorously assess the dye adsorption capabilities. Kinetic modeling revealed that the adsorption process adhered to the pseudo-second-order kinetic model. Remarkably, the prepared beads exhibited impressive adsorption capacities of 26 and 29 mg/g toward methylene blue (MB) and safranin (SF), respectively. SA/HZTO beads have demonstrated excellent adsorption properties, offering a promising avenue for the development of low-cost, efficient, and reusable adsorbent to remove dyes from wastewater.